Factors Associated With DNR Status After Nontraumatic Intracranial Hemorrhage. (July 2020) - Lillemoe, Kaitlyn; Lord, Aaron; Torres, Jose; Ishida, Koto; Czeisler, Barry; Lewis, Ariane
Background: We explored factors associated with admission and discharge code status after nontraumatic intracranial hemorrhage. Methods: We extracted data from patients admitted to our institution between January 1, 2013, and March 1, 2016 with nontraumatic intracerebral hemorrhage or subarachnoid hemorrhage who had a discharge modified Rankin Scale (mRS) of 4 to 6. We reviewed data based on admission and discharge code status. Results: Of 88 patients who met inclusion criteria, 6 (7%) were do not resuscitate (DNR) on admission (aDNR). Do not resuscitate on admission patients were significantly older than those who were full code on admission ( P = 0.04). There was no significant difference between admission code status and sex, marital status, active cancer, premorbid mRS, admission Glasgow Coma scale (GCS), Acute Physiology and Chronic Health Evaluation II (APACHE II) score, or bleed severity. At discharge, 66 (75%) patients were full code (dFULL), 11 (13%) were DNR (dDNR), and 11 (13%) were comfort care. African American and Hispanic patients were significantly more likely to be dFULL than Asian or white patients ( P = .01) and less likely to be seen by palliative care ( P = .004). Patients with less aggressive code status had higher median APACHE II scores ( P = .008) and were more likely to have active cancer ( P = .06). There was no significant difference between discharge code status and sex, age, marital status, premorbid mRS, discharge GCS, or bleed severity. Conclusions: Limitation of code status after nontraumatic intracranial hemorrhage appears to be associated with older age, white race, worse APACHE II score, and active cancer. The role of palliative care after intracranial hemorrhage and the racial disparity in limitation and de-escalation of treatment deserves further exploration.